Design of a Web-Based Air Conditioner Service Information System Using the Fifo (First In First Out) Method: A Case Study at PT. TOP AIRCONDITIONER - Nawari, Mohamad Iqbal; Rafiyudin, Rafiyudin; Heriyansyah, Refki; Assidiqie, Vikri; Darmawan, Nur Cahyo (Journal Collabits, 2025)
PT. Top Airconditioner is one of the companies engaged in AC service and air conditioning providers located at Permata Tangerang Blok DA No.11. PT. Top Airconditioner already has a website that contains information about PT. Top Airconditioner, the types of AC service services available along with their prices, but do not have a special website that functions for booking AC service services because currently the process of booking AC service services is still using WhatsApp media. The system that is currently running is not running well because there is still a problem, namely there is no media to store AC service booking request data because currently the request is made using WhatsApp media so that data is vulnerable to being lost and AC repair reports have not been properly documented because the data of the repair results is only recorded using a book. This study uses the PIECES analysis method, RAD development, UML design, and system testing using blakbox testing. This research results in an ac service system that is built using Java, spring boot, for the Front End using react js postgreSql database and its deployment using google cloud platform.